The Ultrastructure of Sanchytrium tribonematis (Sanchytriaceae, Fungi incertae sedis) Confirms its Close Relationship to Amoeboradix. (31st May 2019) - Karpov, Sergey A.; Vishnyakov, Andrey E.; Moreira, David; López‐García, Purificación
Abstract: Fungi encompass, in addition to classically well‐studied lineages, an ever‐expanding diversity of poorly known lineages that include, among others, zoosporic chytrid‐like parasites. According to recent phylogenetic analysis based on 18S + 28S rRNA concatenated genes two unusual chytrid‐like fungi Amoeboradix gromov i and Sanchytrium tribonematis form a monophyletic group, the family Sanchytriaceae, which represents a new divergent taxon that remains incertae sedis within Fungi. Zoospores of Amoeboradix gromov i contain one of the longest kinetosomes known in eukaryotic cells, which are composed of microtubular singlets or doublets. However, the ultrastructure of S. tribonematis, the type species of the genus had not been yet studied. Here, we provide the results of TEM investigations of zoospores and sporangia from two strains of S. tribonematis . The two strains are endowed with unusual features. Like in A. gromovi, amoeboid zoospores of S. tribonematis contain a long kinetosome composed of microtubular singlets, and the two orthogonal centrioles in their sporangia have nine microtubular singlets with an internal ring. The morphological and ultrastructural features of S. tribonematis are now included in the improved taxonomic diagnosis for this species.